Orthodoxy – the symbolic language of the drama July by Ivan Vyrypaev - Karlikowska-Pąsiek, Magdalena Małgorzata (Journal of Education Culture and Society, 2019)
Aim. The aim of the paper is to interpret and analyse Orthodox symbols through the prism of the Orthodox theology. Methods. The senses of the Orthodox symbolism as proposed by the artist are not always compliant with Orthodox doctrine. Therefore, in order to fully understand the sense of Ivan Vyrypaev’s drama, it is necessary to first decode the Orthodox symbols that make up the language of the work discussed. For this reason, the major Orthodox symbols occurring in July will be listed at the very beginning of the paper. Then, they will be discussed in the context of the Orthodox theology as well as the artist’s own words. This task will contribute to the decoding of the language of I. Vyrypaev’s work. Results. According to I. Vyrypaev, the cruelty of a patient of the Smolensk madhouse is an inverted hierarchy of values which at the same time serves as his path of inquiry. On the other hand, the superficial attitudes, such as good, culture, humanitarianism, liberal values or democracy are obstacles (demons) which he has to overcome in order to find himself and God. The Orthodox symbols in July are allegories by means of which the author wants to show the main hero’s path to the truth. Furthermore, a justification for this way of thinking is one of the mottos that I. Vyrypaev included in July. Conclusions. In the drama July, I. Vyrypaev utilised the following sacral symbols: the theological significance of the Church in the Orthodox faith, the idea of communality, the concept of Orthodox humility as well as the idea of deification and martyrdom. The threads of the Orthodox symbolism used by I. Vyrypaev are superficial and should not be interpreted literally. The author consciously inverts the hierarchy of the Orthodox symbols in his work in order to show the bewilderment and corruption of the modern society. In the drama July I. Vyrypaev is more focused on being inspired by the Orthodox culture than on closely reflecting its senses. The symbolism of the altar and the ideas of martyrdom as applied in July are similar to the Christian symbols in the Roman Catholic approach.